3D printed models for planning endovascular stenting in transverse aortic arch hypoplasia. Issue 6 (12th February 2015) - Valverde, Israel; Gomez, Gorka; Coserria, Jose Felix; Suarez‐Mejias, Cristina; Uribe, Sergio; Sotelo, Julio; Velasco, Maria Nieves; Santos De Soto, Jose; Hosseinpour, Amir‐Reza; Gomez‐Cia, Tomas
<x xml:space="preserve">Abstract</x> Objectives To evaluate whether three‐dimensional (3D) printed models can be used to improve interventional simulation and planning in patients with aortic arch hypoplasia. Background: Stenting of a hypoplastic transverse arch is technically challenging, and complications such as stent migration and partial obstruction of the origin of the head and neck vessels are highly dependent on operator skills and expertise. Methods: Using magnetic resonance imaging (MRI) data, a 3D model of a repaired aortic coarctation of a 15‐year‐old boy with hypoplastic aortic arch was printed. Simulation of the endovascular stenting of the hypoplastic arch was carried out under fluoroscopic guidance in the 3D printed model, and subsequently in the patient. A Bland–Altman analysis was used to evaluate the agreement between measurements of aortic diameter in the 3D printed model and the patient's MRI and X‐ray angiography. Results: The 3D printed model proved to be radio‐opaque and allowed simulation of the stenting intervention. The assessment of optimal stent position, size, and length was found to be useful for the actual intervention in the patient. There was excellent agreement between the 3D printed model and both MRI and X‐ray angiographic images (mean bias and standard deviation of 0.36 ± 0.45 mm). Conclusions: 3D printed models accurately replicate patients' anatomy and are helpful in planning endovascular stenting in transverse arch hypoplasia. This opens a door for potential simulation applications of 3D models in the field of catheterization and cardiovascular interventions. © 2015 Wiley Periodicals, Inc. © 2015 Wiley Periodicals, Inc.